Problem-oriented policing of transnational environmental crimes: a social harms approach - Kailemia, Mwenda (International journal of comparative and applied criminal justice, 2019)
Since the publication of Herman Goldstein’s seminal article on Problem-oriented Policing (POP) in 1979, criminologists have attempted to apply its proactive methodology, with a large body of police work concentrating on how operational policing can benefit from the methodologies of POP, and specifically how events are recognised, approached and resolved as policing problems. Even then, most of these works ascribe a non-existing ontological value to events, supposing a bad actor against whom the good actor intervenes. This atomised, state-centrist notion of criminality has been discredited by social harms theory, which emphasises a reading of crime that reaches beyond the bureaucratic abilities of state criminal justice agencies. This article is aimed at illustrating how both POP and a social harms approach to crime can enrich each other, especially with regard to environmental crimes.